A program of circuit resistance training under hypobaric hypoxia conditions improves the anaerobic performance of athletes - Álvarez-Herms, J.; Julià-Sánchez, S.; Corbi, F.; Pagès, T.; Viscor, G. (Science & Sports, 2016)
Objective: Training high-living low model has been studied as an intermittent hypoxic training (IHT) for anaerobic performance improvement. To test the hypothesis that a high-intensity circuit strength training (CST) performed in hypoxia increases the anaerobic running performance at sea level. Equipment and methods: Twelve sub-elite male 400-m runners were divided into two groups: hypoxia (HYP) (n = 6) and control (NOR) (n = 6). Twelve sessions were performed over a period of four weeks (three days/week) without any additional running training. Hypobaric training was performed at a simulated altitude of 3000 m (700 hPa; 10.15 PSI). The anaerobic running performance was tested with a repeated interval running training (RIR). Based on an "all-out" 300-m test performed before and after CST, the subjects performed as many sets as they could at 90% of the individual maximal speed reached with a three-minute rest period between sets. Results: As compared to controls, the HYP group showed the following responses post CST: RIR +20.5% (number of sets) (P < 0.03); (HYP: 4.3 ± 1 to 6.6 ± 1.9 vs. NOR: 3.6 ± 1 to 4.6 ± 1.3), maximal lactate accumulation (in the last set) +8.1% (P < 0.03) (HYP: 11.8 ± 1 to 15.7 ± 1.3 vs. NOR: 12.5 ± 0.9 to 14.6 ± 1.6). Maximum and recovery heart rates finishing the test and hematology did not show statistically significant differences (P > 0.05). However, CST in HYP showed a higher HRavg (152.6 ± 6.2) than sea level training (144.4 ± 5.1) (P < 0.01). Conclusions: These data indicate that a CST in hypoxia conditions increases the anaerobic performance in trained athletes.